2016
DOI: 10.3233/jcb-15022
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione loaded solid lipid nanoparticles: Preparation and in vitro evaluation as delivery systems of the antioxidant peptide to immunocompetent fish cells

Abstract: BACKGROUND: Solid lipid nanoparticles (SLN) have not been used for peptide supply to fish cells. OBJECTIVE: To evaluate the potential of SLN to deliver the antioxidant glutathione (GSH) to the primary cultures of head-kidney (HK) leucocytes of Sparus aurata L. METHODS: SLN were produced using the amphiphilic lipid Gelucire ® 50/13 according to the melt-emulsification method. In vitro stability and colorimetric studies for the antioxidant activity were carried out prior to biological assays on HK leucocytes. RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Freshly prepared GSE-loaded SLN were evaluated for their particle stability at two different temperature conditions (4 and 37 °C) [ 18 ] by incubating the particles without any stirring. Precisely, at 4 °C solvent was double distilled water and particles were incubated up to 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…Freshly prepared GSE-loaded SLN were evaluated for their particle stability at two different temperature conditions (4 and 37 °C) [ 18 ] by incubating the particles without any stirring. Precisely, at 4 °C solvent was double distilled water and particles were incubated up to 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…Kadari et al ( 61 ) found that angiopep-2-modified SLN was an excellently targeted drug delivery system for glioma therapy. SLN could be used to transport antioxidant glutathione (GSH) to immunocompetent fish cells, and the antioxidant activity of GSH in vitro is stable in the transport process ( 62 ).…”
Section: Solid Lipid Nanoparticles Applied In Bioactive Peptide Deliverymentioning
confidence: 99%
“…All pellets resulting from centrifugation were used for the following studies. Unloaded SLNs were prepared following the same procedure described above in (i) without any addition of any GSE to the aqueous phase [8,9,54].…”
Section: Preparation Of Slnmentioning
confidence: 99%
“…Among the colloidal carriers, solid lipid nanoparticles (SLN) have been shown to have several benefits, including enhanced safety and stability, and controlled drug release, and can be prepared on a large scale according to scale-up industrial guidelines. In our laboratory, we have already investigated SLNs made of a single lipid, namely Gelucire ® 50/13, for uptake in fish cell lines in order to ascertain the possible immunological applications, and by ex vivo investigations, the biocompatibility of such a synthetic lipid was assessed [7][8][9]. From a chemical viewpoint, it could be assumed that using two or more lipids may be better than using only one.…”
Section: Introductionmentioning
confidence: 99%